Performansi Green Inhibitor Berbasis Ekstrak Propolis Kele-Kele Terhadap Laju Korosi Sambungan Las Pipa Sch 40 Pada Medium Korosif Nacl 3.5% - Suastika Jaya, I Made; Budiarsa, I Nyoman; Putra Negara, Dewa Ngakan Ketut (Teknik Desain Mekanika; Vol 10 No 4 (2022): Oktober 2022 : Teknik Desain Mekanika, 2022)
Abstract Corrosion is a condition in which a metal experiences a decrease in quality caused by an electrochemical reaction to its environment. Efforts to control and periodic maintenance is an important factor in the prevention of corrosion. There are various ways of controlling corrosion and one of them is the use of corrosion inhibitors based on natural materials. Natural materials were chosen because they are friendly to the environment, easy to obtain, and relatively inexpensive. In the propolis Trigona Sp. There are antioxidant compounds which include phenolic compounds and flavonoids. Propolis which is friendly to the environment can be used as a corrosion inhibitor based on natural materials in an effort to control corrosion in welding joints of Sch 40 pipes in a corrosive environment of 3.5% NaCl. In this study, the theory of weight loss was used according to ASTM G31 – 72 guidelines, with variations in the addition of 0, 4, 6, 8 ml of inhibitor with a soaking time of 336 hours. Then observed the corroded surface morphology with microstructure photos, FTIR testing to determine the content contained in propolis. The results obtained showed that the corrosion rate decreased in the 4 ml inhibito variation with a value of 1.374 mpy, with the addition of 6 ml inhibitor it became 1.148 mpy and the peak was in the 8 ml inhibitor variation with a corrosion rate value of 0.903 mpy and the efficiency of the inhibitor was found in the addition of 8 ml inhibitor with an efficiency of 84%. This shows the propolis extract inhibitor Trigona Sp. (Balinese kele-kele) deserves to be called Green Inhibitor. Keywords: Sch 40 pipe; Propolis; Trigona Sp.; Organic inhibitors; Weight loss method; NaCl 3,5%